Foreign Exchange, Gold, and Real Estate Markets in India: An Analysis of Return Volatility and Transmission - Mishra, Amritkant (Indian Journal of Finance, 2019)
This empirical analysis endeavored to investigate the return volatility, covolatility, and the spillover impact of gold, real estate, and U.S. dollar in India. The generalized autoregressive conditional heteroskedasticity dynamic conditional correlation (GARCH - DCC) was used to reveal the return volatility and conditional correlation. The volatility spillover was examined by using the variance decomposition technique. The empirical outcome clearly revealed the presence of ARCH and GARCH effect on gold, realty, and U.S. dollar. Additionally, the results also manifested that the returns of these variables were not moving away from their means in the long run. On the other hand, the consequences of volatility spillover reported that real estate was the most dominating among all markets. This is so because returns on real estate had a significant contribution to the return volatility of the other markets. Finally, it was also found that return volatility of U.S. dollar was most affected as it was the net receiver of volatility, while return volatility of gold seemed to be neutral in the Indian financial market.